NEXUS BETWEEN HUMAN CAPITAL ACCUMULATION AND ECONOMIC GROWTH - Kausar, Tayyiba; Iqbal, Faisal; Ramirez-Asis, Edwin; Asnate-Salazar, Edwin Johny; Loli-Poma, Telmo Pablo (The journal of contemporary issues in business and government, 2021)
Present study examines the effect of human capital accumulation and its influencing variables such as expenditure on education and quality of education, labor force, free trade and investment and its impact on economic development which can be measured in terms of Gross Domestic Product and GDP per capita. The data for the current study is comprised of economic indicators from almost 181 countries around the globe while using the panel technique. The outcome of the study suggest that enhancing the quality level of education through increasing the budget expenditure for education sector will result in capable work force which will in turn promote the economic growth of our country, similarly funds reimbursements towards fixed capital and free trade are also major determinants of economic development. The present study is also unique in terms of data collection from a vast number of countries to generate the empirical findings related to the topic.